The ergogenic effect of beta-alanine combined with sodium bicarbonate on high-intensity swimming performance - de Salles Painelli, V.; Roschel, H.; de Jesus, F.; Sale, C.; Harris, R. C.; Yázigi Solis, M.; Braga Benatti, F.; Gualano, B.; Lancha Jr, A. H.; Artioli, G. G. (Applied Physiology, Nutrition, and Metabolism, 2013)
We investigated the effect of beta-alanine (BA) alone (study A) and in combination with sodium bicarbonate (SB) (study B) on 100- and 200-m swimming performance. In study A, 16 swimmers were assigned to receive either BA (3.2 g/day for 1 week and 6.4 g/day for 4 weeks) or placebo (PL; dextrose). At baseline and after 5 weeks of supplementation, 100- and 200-m races were completed. In study B, 14 were assigned to receive either BA (3.2 g/day for 1 week and 6.4 g/day for 3 weeks) or PL. Time trials were performed once before and twice after supplementation (with PL and SB), in a crossover fashion, providing 4 conditions: PL-PL, PL-SB, BA-PL, and BA-SB. In study A, BA supplementation improved 100- and 200-m time-trial performance by 2.1% (p = 0.029) and 2.0% (p = 0.0008), respectively. In study B, 200-m time-trial performance improved in all conditions, compared with presupplementation, except the PL-PL condition (PL-SB, +2.3%; BA-PL, +1.5%; BA-SB, +2.13% (p < 0.05)). BA-SB was not different from BA-PL (p = 0.21), but the probability of a positive effect was 78.5%. In the 100-m time-trial, only a within-group effect for SB was observed in the PL-SB (p = 0.022) and BA-SB (p = 0.051) conditions. However, 6 of 7 athletes swam faster after BA supplementation. The probability of BA having a positive effect was 65.2%; when SB was added to BA, the probability was 71.8%. BA and SB supplementation improved 100- and 200-m swimming performance. The coingestion of BA and SB induced a further nonsignificant improvement in performance.